The immune factors have complex causal regulation effects on bone mineral density - Cao, Rong-Rong; Yu, Xing-Hao; Xiong, Meng-Fei; Li, Xue-Ting; Deng, Fei-Yan; Lei, Shu-Feng (Frontiers in Immunology, 2022)
Recent evidence has gradually recognized that immune system and skeletal system are two closely correlated systems, but the specific immune factors on bone mineral density (BMD) are largely unknown. Based on the summary-level data of genome-wide association studies (GWASs), we performed a series of analyses including two-sample Mendelian Randomization (MR) analysis to test potential causal links between 731 immune traits [including median fluorescence intensities (MFIs), absolute cell (AC) counts, relative cell (AC) counts, and morphological parameters (MP)] and BMD. After false discovery rate (FDR) correction, 9 MFI-, 16 AC-, 22 RC-, and 5 MP-BMD pairs reached the level of significance (FDR-adjust P < 0.05). For MFI traits, the T and B cell panels had the largest number of significant immune trait pairs than other panels. CD40, as a molecule expressed by 4 subsets of monocytes, was highlighted due to its consistently positive correlation with BMD at four sites. For both AC and RC traits, immune traits from the T-cell panel were also highlighted, with CD39-positive T-cell subsets being the most frequently observed feature. For MP traits, the most significant association immune trait with BMD was SSC-A on CD14+ monocyte. Sensitivity analyses suggested that the identified immune factors were robust to pleiotropy. Multivariable MR analysis conformed independent causal effect of several immune traits on BMD. Mediation analyses showed that CD40 on monocytes could mediate multiple immune traits, especially the suggestive associations of CD27 on several memory B cells with BMD mediated by CD40 on CD14+ CD16- monocyte. Our study represents the first systemic evaluation for the causal effects of immune traits on risk of osteoporosis. The findings highlighted the complex and important role of immune-derived factors in the pathogenesis of osteoporosis.